Measurement of the tt¯Z and tt¯W production cross sections in multilepton final states using 3.2 fb−1 of pp collisions at s√ = 13 TeV with the ATLAS detector - Aaboud, M. (2017)
A measurement of the t t  ̄ Z and t t  ̄ W production cross sections in final states with either two same-charge muons, or three or four leptons (electrons or muons) is presented. The analysis uses a data sample of proton?proton collisions at s = 13 TeV recorded with the ATLAS detector at the Large Hadron Collider in 2015, corresponding to a total integrated luminosity of 3.2 fb −1 . The inclusive cross sections are extracted using likelihood fits to signal and control regions, resulting in σ t t  ̄ Z = 0.9 ± 0.3 pb and σ t t  ̄ W = 1.5 ± 0.8 pb, in agreement with the Standard Model predictions.